The Implementation of Electronic Evidence Presentation in Civil Proceedings - Muzammil Siddiqi; Ilyas Ilyas (Graha Primera Saintifika, 2025)
As judicial systems increasingly adopt digital technologies, Indonesia’s Supreme Court has introduced e-litigation to streamline court procedures, including the presentation of electronic evidence in civil cases. This study investigates how electronic evidence is implemented at the Banda Aceh District Court, based on Supreme Court Regulation No. 1 of 2019. The regulation requires parties to submit documentary evidence through an e-court system and permits the examination of witnesses or experts via teleconference. Although the implementation complies with legal provisions, it faces several challenges. These include a lack of detailed procedural guidance, leading to legal uncertainty, and practical issues such as unreliable internet connectivity and limited user familiarity with digital systems. In response, the court has undertaken efforts such as upgrading network infrastructure and conducting training programs. The study concludes by recommending clearer procedural standards and enhanced technological and human resource support to improve the effectiveness of electronic evidence presentation in civil proceedings.